2021
DOI: 10.2174/1745017902117010092
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Distance Learning and E-learning in Students with Learning Disabilities: A Review on the Effects and some Hint of Analysis on the Use during COVID-19 Outbreak

Abstract: Even if the use of distance learning and E-learning has a long tradition all over the world and both have been used to keep in contact with students and to provide lessons, support and learning materials, there is an open debate on the balance between advantages and disadvantages in the use of distance learning. This debate is even more central in their use to support students with Learning Disabilities (LDs), an overarching group of neurodevelopmental disorders that affect more than 5% of students. The curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 58 publications
1
38
0
5
Order By: Relevance
“…It is worth mentioning, however, that distance learning (and information and communication technology, in general) may benefit students with learning disabilities, providing them an environment where they can gain motivation, engagement, and interest, and which benefits their attention and the cooperation between students [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning, however, that distance learning (and information and communication technology, in general) may benefit students with learning disabilities, providing them an environment where they can gain motivation, engagement, and interest, and which benefits their attention and the cooperation between students [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…When conducting the study, we found no standardized e-learning templates for SWD, except a few e-learning templates and quite a few recommendations [9,30,51]. However, it is very important to adhere to the provisions of the ETSI standard when creating e-learning materials and to consider that a multidisciplinary approach is then needed in designing, developing, and providing learning environments, learning materials and in the use of tools and devices if the aim is to consider all specific requirements in SWD e-learning [5].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when students with disabilities (SWD) are in question, they are increasingly reporting on specific learning disabilities [4]. Over 10% of students have reported at least one special educational need (SEN), and over 5% have learning disabilities/disorders (LDs) (an overarching group of neurodevelopmental disorders that affect the development of primary and/or secondary academic abilities) [5]. also whether there is an effective standardized e-learning course template for SWD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite a considerable amount of research in the digital healthcare field dealing with students' education as well as with health preventive strategies, high-quality evidence on e-learning for professionals remains scarce [22,[35][36][37]. Therefore, further research is needed especially considering training for professionals-and more specifically for professionals working with children.…”
Section: Recommendations From the Erica Novel E-learning Frameworkmentioning
confidence: 99%